Prevalence of Vancomycin-resistant enterococci (VRE) in Egypt (2010-2022): a systematic review and meta-analysis - Ahmed Azzam; Hoda Elkafas; Heba Khaled; Ahmed Ashraf; Mohammed Yousef; Aya Awny Elkashef (SpringerOpen, 2023)
Abstract Background Vancomycin-resistant Enterococci (VRE) represent a critical medical and public health concerns due to their association with serious nosocomial infections and a high risk of mortality. We aimed to reveal the pooled prevalence of VRE and antimicrobial resistance profiles among enterococci clinical isolates in Egypt. Methods A PubMed, Scopus, Google Scholar, and Web of Science literature search was carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. Only published studies documenting the prevalence of VRE between 2010 and 2022 were included. Using the random effects model and the 95% confidence intervals, the pooled estimate of VRE was calculated by MedCalc Version 20.113. Cochran's Q and I 2 tests were used to evaluate the degree of heterogeneity, and publication bias was examined by visually examining the funnel plot and its associated tests (Begg's and Egger's tests). Results The pooled prevalence of VRE among enterococci clinical isolates in Egypt was estimated to be 26% (95% CI 16.9 to 36.3). E. faecalis had a greater pooled prevalence than E. faecium, with 61.22% (95% CI 53.65 to 68.53) and 32.47% (95% CI 27 to 38.2), respectively. The VanA gene is more frequent than the VanB gene among VRE, with a pooled prevalence of 63.3% (95% CI 52.1 to 73.7) and 17.95% (95% CI 7.8 to 31), respectively. The pooled resistance rate of linezolid was substantially lower than that of ampicillin and high-level gentamicin (HLG) 5.54% (95% CI 2.33 to 10%), 65.7% (95% CI 50.8 to 79.2%), and 61.1% (95% CI 47.4 to 73.9), respectively. Conclusion The prevalence of VRE is alarmingly high in Egypt. It is imperative that antimicrobial stewardship activities and infection control programs are strictly adhered to and implemented to prevent further escalation of the problem.